Pour mieux comprendre le fonctionnement de l’alternance modale en rapport avec la variation des diatheses dans les structures subordonnees substantives en espagnol - Victor Nguepi, George (Círculo de Lingüística Aplicada a la Comunicación, 2023)
Syntax organisation of subordinated clauses and terminological precisions, in addition with the question of diathesis variation considered by Spanish traditional grammar till recent date as synonym of voice, is a serious pedagogical problem usually faced by all teachers of that language in their daily teaching. However, substantive subordinated clauses as regard to relative and adverbial ones, as argument of the verb of main clause, offers clac 21/2005 22 opportunity to re-examine the configuration and differences which, although considered very often as very intellectual, give the opportunity to better understand the content and specificities of each of these structures.